EVIDENCE BASED CASE REPORT (EBCR) : TEKNIK MOKSIBUSI PADA ANAK DENGAN DIARE (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background: In Indonesia, diarrhea is one of the main health cases as a cause of death for infants and children. The death rate from diarrhea is increasing. This is because there are many risk factors for diarrhea around us. Moxibustion is a therapy that can be used to treat diarrhea by burning dry herbs near the skin. Purpose: This therapy aims to warm, strengthen, and stimulate blood flow, strengthen the kidneys, expel wind and cold and dissolve stagnation. Method: This study aims to determine the effect of the moxibustion technique on the cure of diarrhea in children using a literature review method approach. Result: The results of the study showed that the moxibustion technique was effective for treating diarrhea. This technique works by warming the acupuncture points which aims to dilate blood vessels so that blood circulation is smooth, this will provide optimal oxygen supply so that blood circulation is smoother, the body is healthy, and minimizes the occurrence of inflammation in the blood vessels, swelling, pain, and discomfort. uncomfortable. Conclusion: Moxibustion therapy was successfully applied to patients with a.n W who experienced acute diarrhea with an intensity of 3 times. This therapy can reduce the intensity of diarrhea.